Ethnicity in censuses: Changeable and inconstant category - Mrđen Snježana (Stanovništvo)
The issue of ethnicity was set in all censuses of SFRY, as well as in the first censuses in countries that were created after its disintegration. When analyzing the censuses it can be concluded that it is a changeable category. Not only was the manner of forming the question in censuses changing, but also the number of categories of nationality and their order in published census' results. It depended on state policy and the political situation preceding the censuses. Since the answer on the issues of ethnicity is a subjective criterion, and it was written down according to the freely declared statement of the residents, guaranteed by the Constitution. It has often happened that same individuals have declared themselves differently from one census to another, and also some categories of ethnicity have vanished and some others were created. Although in SFRY nations and ethnicities were equal, still indirectly in published results, existence of these two categories was indicated. But, in newly created countries, the manner of forming the question of ethnicity was changed, their number and order were also changed and the notion of 'minority' was again introduced, indicating, beyond doubt, a different status of nationality (except the majority) from the one in the former Yugoslavia.